Factors Influencing Organizational Citizenship Behavior Of The New Generation Of Employees In China: The Roles Of Positive Emotion As Mediator And Lmx As Moderator - Fu, Yunneng (2023)
Along with the flourishing electronic commerce (e-commerce) and economic globalisation, the social economy has experienced profound changes and accelerated progress. Employees with organisational citizenhip behaviour (OCB) contribute to the accomplishment of social and economic in the organisation. Unfortunately, the new generation of employees, being the core human resources of Internet companies are less likely to engage in OCB. They generally have a lack of collective concept, weak sense of responsibility, low organisational loyalty and identity, short average working life, and high turnover rate. These issues may be detrimental to organisational development and performance. The purpose of this study is to explore the influencing factors of improving OCB among the new generation of employees. As such, this study looked into several ways to resolve issues lurking in the new generation of employees. The theories deployed in this study are positive psychology, selfdetermination theory, and social exchange theory. From the stance of positive psychology, positive leadership (PL), organisational climate (OC), and psychological capital (PC) were selected as independent variables. Meanwhile, positive emotion (PE) and leader-member exchange (LMX) served as the mediating and moderating variables, respectively, to examine the impact towards organisational citizenship behaviour (OCB).